Cynara scolymus L. A promising Mediterranean extract for topical anti-aging prevention - Marques, P. (2017)
Cynara scolymus L. (CS), usually known as globe artichoke, is a Mediterranean plant with antioxidant properties due to its content of polyphenols, including caffeoylquinic and dicaffeoylquinic acids. The use of bioactive ingredients or phytochemicals extracted from plant tissues in cosmetics is increasing, thus artichoke extract due to its promising constituents can be incorporated in topical formulations. The aim of this study was the chemical characterization of different CS extracts in order to investigate the antioxidant and the sun protection potential in topical formulations. Aqueous extracts were analyzed by HPLC to quantify target compounds, such as cynarin, chlorogenic acid and cynaroside. Antioxidant activity by DPPH assay and ROS scavenging activity in HaCaT cells, as well as cytotoxicity assays and sun protection factor were assessed. The results showed that CS extract and CSC fraction, one of the purified fractions, were rich in polyphenols and presented antioxidant and photoprotective activity. Then, both fractions were incorporated in two topical formulations: O/W emulsion and hydrogel. Physicochemical characterization, microbiological control, cytotoxicity assays and ROS scavenging activity in HaCaT cells were performed to ensure the quality, safety and efficacy of the products developed. In vivo studies, Human Repeat Insult Patch Testing and an assay to determine their antioxidant capacity, were also performed. Besides the excellent antioxidant and photoprotective activity, the final formulations proved to be also suitable and safe for topical use.